Der Zugangsanspruch des Betriebsrats zu bestimmten Bereichen innerhalb des Betriebs: Eine Untersuchung hinsichtlich der dogmatischen Grundlage, der Voraussetzungen und der Grenzen des Anspruchs - Schiller, Julian Vincent (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
The book deals with the controversial question of the dogmatic basis of the works committee's right of access and provides its own solution. Accordingly, the right results from a further development of the law with respect to the works committee’s general right to information regulated in Section 80 (2) BetrVG. Based on Section 80 (2) BetrVG, it is examined to which extent the substantive and formal requirements of the general right to information can be transferred to the right of access. Furthermore, it is examined to what extent the rights and legal interests of third parties, in particular company procedures, mandatory safety regulations and the protection of trade secrets, limit the right of access.